A Singleton Infant with Bilateral Renal Agenesis and Normal Pulmonary Function - Lovya George; Winston Manimtim; Jotishna Sharma (Case Reports in Pediatrics)
Bilateral renal agenesis leads to anhydramnios and other sequelae including pulmonary hypoplasia. There have been rare case reports of normal pulmonary function in the presence of bilateral renal agenesis in monoamniotic discordant twins, but this has never been reported in a singleton pregnancy. The few reported cases in twins have all been fatal in the neonatal period with no reported cases of survival beyond 2 months. We describe the first case of a singleton infant with bilateral renal agenesis who had normal pulmonary function and did well on peritoneal dialysis for 4 years while awaiting a renal transplant.